Hubungan Faktor Ekonomi, Pengetahuan Ibu dan Pemberian Asi Ekslusif dengan Kejadian Stunting di UPT Puskesmas Kota Soe - Sheren O. Nesimnasi; R. Pasifikus Ch. Wijaya; Afrona E. L. Takaeb (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Stunting, a chronic malnutrition problem and is still one of the health problems in the work area of ​​UPT Puskesmas Kota Soe. The incidence of stunting is influenced by various direct and indirect factors. This study aims to analyze the relationship between economic factors, namely family income, maternal knowledge about nutrition and exclusive breastfeeding with the incidence of stunting in the work area of ​​UPT Puskesmas Kota Soe. This study used a case control survey design. The sample in this study amounted to 62 respondents, consisting of 31 case samples and 31 control samples. The sampling technique used was simple random sampling. Data analysis used univariate and bivariate analysis with the chi square test with a confidence level of 95% (α = 0.05). The results of this study indicate that the factors related to the incidence of stunting are maternal knowledge about nutrition p = 0.001 (OR = 7.20) and exclusive breastfeeding p = 0.011 (OR = 4.41), while economic factors, namely family income, have no relationship with the incidence of stunting p = 0.075. Lack of maternal knowledge about nutrition is one of the causes of stunting, so it is hoped that mothers who have toddlers will participate to broaden their horizons in meeting their children's nutritional needs.